Usability Assessment of Technologies for Remote Monitoring of Knee Osteoarthritis - Andrea Cafarelli; Angela Sorriento; Giorgia Marola; Denise Amram; Fabien Rabusseau; Herve Locteau; Paolo Cabras; Erik Dumont; Sam Nakhaei; Ake Jernberger; Par Bergsten; Paolo Spinnato; et al. (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: To evaluate the usability of different technologies designed for a remote assessment of knee osteoarthritis. Methods: We recruited eleven patients affected by mild or moderate knee osteoarthritis, eleven caregivers, and eleven clinicians to assess the following technologies: a wristband for monitoring physical activity, an examination chair for measuring leg extension, a thermal camera for acquiring skin thermographic data, a force balance for measuring center of pressure, an ultrasound imaging system for remote echographic acquisition, a mobile app, and a clinical portal software. Specific questionnaires scoring usability were filled out by patients, caregivers and clinicians. Results: The questionnaires highlighted a good level of usability and user-friendliness for all the technologies, obtaining an average score of 8.7 provided by the patients, 8.8 by the caregivers, and 8.5 by the clinicians, on a scale ranging from 0 to 10. Such average scores were calculated by putting together the scores obtained for the single technologies under evaluation and averaging them. Conclusions: This study demonstrates a high level of acceptability for the tested portable technologies designed for a potentially remote and frequent assessment of knee osteoarthritis.